Chemical‐Labeling‐Assisted Detection of Nucleobase Modifications by Quantum‐Tunneling‐Based Single‐Molecule Sensing. (22nd October 2019) - Furuhata, Takafumi; Ohshiro, Takahito; Izuhara, Yuichi; Suzuki, Tomoaki; Ueki, Ryosuke; Taniguchi, Masateru; Sando, Shinsuke
Abstract: Quantum‐tunneling‐based DNA sensing is a single‐molecule technique that promises direct mapping of nucleobase modifications. However, its applicability is seriously limited because of the small difference in conductivity between modified and unmodified nucleobases. Herein, a chemical labeling strategy is presented that facilitates the detection of modified nucleotides by quantum tunneling. We used 5‐Formyl‐2′‐deoxyuridine as a model compound and demonstrated that chemical labeling dramatically alters its molecular conductance compared with that of canonical nucleotides; thus, facilitating statistical discrimination, which is impeded in the unlabeled state. This work introduces a chemical strategy that overcomes the intrinsic difficulty in quantum‐tunneling‐based modification analysis—the similarity of the molecular conductance of the nucleobases of interest. Abstract : Chemistry‐assisted nanogap sensing : Single‐molecule electrical detection of modified nucleobases by a solid‐state nanogap is enabled by chemical labeling to differentiate its conductivity from that of canonical nucleobases. This is rationally achieved by modulation of the HOMO level and suggests the applicability of this strategy to broader base modification analysis.